Copper‐Assisted Synthesis of Novel Pyrazolo[3, 4‐d]thiazoles. Issue 15 (4th July 2019) - Ostache, Nicu‐Cosmin; Hiebel, Marie‐Aude; Fînaru, Adriana‐Luminiţa; Guillaumet, Gérald; Suzenet, Franck
Abstract: Based on both the chemical and the biological importance of the pyrazole and the thiazole backbones, we report herein a convenient design of new pyrazolo[3, 4‐ d ]thiazoles for the development of molecules with a high therapeutic potential. The effective and appropriate strategy chosen consists of an intramolecular copper‐catalysed N ‐arylation followed by the Liebeskind‐Srogl cross‐coupling reaction. The efficiency of copper and palladium catalysts for the first step of the synthesis was evaluated. These efforts allowed the synthesis of a variety of modulated heterobicycles. Abstract : Copper can do it : An efficient one‐pot methodology involving copper‐mediated intramolecular N ‐arylation followed by the Liebeskind‐Srogl cross‐coupling reaction led to an original library of bifunctionalized pyrazolo[3, 4‐ d ]thiazoles with good to excellent yields.